Platelets engage mast cells in a bilateral IL-33-driven feed-forward loop - Airi Nishida; Jun Nagai; Madeline Hastings; Kendall Zaleski; Marie Sasaki; Omar Samir; Juying Lai; Sofia A. Marshall; Hiroaki Hayashi; Sreyashi Majumdar; Kinan Alhallak; Chunli Feng; et al. (Proceedings of the National Academy of Sciences, 2025)
Platelets amplify type 2 inflammation (T2I) through incompletely understood mechanisms. Depletion of platelets markedly attenuated mast cell (MC) activation in a model of aspirin exacerbated respiratory disease (AERD) that depends on IL-33 and cysteinyl leukotrienes (cysLTs). We demonstrate an IL-33-driven feed-forward loop between platelets and MCs. IL-33 neutralization prevented increases in cysLTs and CXCL7, a platelet activation marker, in bronchoalveolar lavage (BAL) fluid from AERD-like mice in response to aspirin challenges. BAL fluid concentrations of PGD 2 correlated strongly with both CXCL7 and MC tryptase in subjects with severe asthma. Platelets amplified PGD 2 and LTC 4 productions by IL-33-stimulated mouse bone marrow–derived MCs (BMMCs), which induced release of CXCL7 and expression of CD62P by platelets. Deletions of MC-specific LTC 4 or platelet-specific type 2 cysLT receptor (CysLT 2 R) completely eliminated both platelet activation and the amplification of PGD 2 and LTC 4 generation by MCs. Platelet-derived ADP/ATP and MC-associated P2Y 1 receptors were essential. These findings identify an innate immune pathway involving MC–platelet interplay that may drive IL-33-dependent immunopathology in asthma.